Intraindividual variation of running economy in highly trained and moderately trained males - Pereira, M. A.; Freedson, P. S. (International Journal of Sports Medicine, 1997)
Previous studies of intraindividual variation in running economy have not compared within-subject variability between groups of runners differing in training level, nor have they considered the workload of the submaximal but relative to the lactate breakpoint. Therefore, the purpose of the present study was to assess intraindividual variation in submaximal oxygen consumption (VO2) during steady rate treadmill running below the lactate breakpoint in highly trained (n = 7) and moderately trained (n = 8) male runners. Subjects completed a discontinuous VO2 max protocol with blood sampling to determine the lactate breakpoint. Three 15 minute level treadmill bouts at approximately 88% of the lactate breakpoint were then performed. Time of day, day of the week, diet, and and footwear were controlled within each subject across the three tests. Statistically significant differences were found between groups in VO2 max, relative fat, training mileage, and 10 km race time (p < 0.01), while the lactate breakpoint was similar between groups (integral of 80% of VO2 max). The difference in treadmill speed between highly trained and moderately trained runners for the submaximal bouts was statistically significant (p < 0.01) and correlated with reported training paces (r = 0.82). Although the mean coefficient of variation for steady rate VO2 was smaller for the highly trained group, the difference was not statistically significant (highly trained = 1.77%, moderately trained = 2.00%; p > 0.05). The mean coefficient of variation for all 15 subjects was 1.90%. After accounting for technological error, biological variation was found to comprise approximately 94% of the intraindividual variation in running economy. In comparison to other studies, these results suggest that workloads below the lactate breakpoint may allow more stable measures of running economy to be obtained.